LEGAL ANALYSIS OF THE CRIMINAL ACTS OF DOMESTIC VIOLENCE: DECISION NO. 101.Pid.Sus/2023/PN - Lukman, Ulfi; Januardi, Hengk; Chairil, Aisyah; Budi, Dio Prasetyo; Arifin, Mohammad Daniel (Universitas Airlangga, 2025)
The main problem in this thesis is about the crime of domestic violence with the object of analysis in the case of Decision No. 101/Pid.Sus/2023/PN.Kbr. And to find out the judge's legal considerations in imposing criminal sanctions on perpetrators of criminal acts of domestic violence committed by husbands against wives in decision no. 101/Pid.Sus/2023/PN.Kbr. The research used to answer the two things above is literature research on decisions and the author took data obtained from court decisions in the form of interviews with one of the judges at the Koto Baru District Court. The aim of this thesis is to find out about criminal acts of domestic violence both under Islamic criminal law and under Law Number 23 of 2004, then to find out the application of legal considerations made by the judge in imposing a sentence on the defendant. The results of this research indicate that the application of material criminal law to criminal acts in the judge's decision in case no. No. 101/Pid.Sus/2023/PN.Kbr. In accordance with the legislation in this case regulated in law number 23 of 2004 concerning the elimination of domestic violence in handing down criminal sentences the judge has given considerations in accordance with the facts and those revealed in court both in terms of material criminal and formal criminal considerations.